Resistance to Airflow through Bulk Grains, Oilseeds and Other Agricultural Products – A Review - Moses, J. A.; Jayas, D. S.; Alagusundaram, K. (Journal of Agricultural Engineering, 2014)
Stored grain bulks are man-made ecosystems subject to incessant interactions among several biotic and abiotic factors. Temperature and moisture are of prime concern which can be manipulated to preserve grains through aeration and drying systems. To properly design these systems, there is a need to understand the relationship between resistance to airflow through different bulk grains (expressed as pressure drop per unit length) and airflow. The paper outlines the factors that affect the resistance to airflow, and highlights the scope of mathematical modelling in this context. Recent advancements and future research needs have been highlighted.